The world's most popular manga dragon ball : heaven and earth - Toriyama, Akira (San Francisco : VIZ Media, 2021)
Goku is the world's only hope--the only being on Earth capable of fighting Piccolo, the Great Demon King! But the city-demolishing battle ends with Piccolo birthing a younger, even tougher version of himself, who will return in three years time to finish the destruction wrought by his father! In search of a way to defeat the new Piccolo, Goku's gaze turns skyward--to the heavenly realm of Kami-sama, creator of the Dragon Balls, deity of the Dragon Ball world. But Piccolo and Kami-sama share a shocking secret ..
VOL 14
Keywords: Comic books, strips